Posted by Ren on Saturday, October 16, 2010 at 12:01am.
x + y = 5,
3x - 5y = -1,
I will use the elimination method which
eliminates 1 variable and allows me to solve for the other.
Step 1. Multiply both sides of the 1st Eq by -3 and add the 2 Eqs:
-3x - 3y = -15,
3x - 5y = -1,
0 - 8y = -16,
- 8y = - 16,
Step 2. Divide both sides by -8 and get:
y = 2.
Step 3. Substitute 2 for y in Eq 1
and solve for x:
x + 2 - 5,
x = 5 - 2,
x = 3.
Solution set:(x , y) = (3 , 2) = The
point where the 2 graphs will intersect.
To graph the Eqs, use the following
convenient points:
x + y = 5. (0 , 5) , (2 , 3) , (5 ,0).
3x - 5y = -1. (-2 , -1) , (3 , 2) ,
(5 , 3.2).
I hope this will help.
CORRECTION: The 1st Eq under Step 3
should read: x + 2 = 5.